Peran Guru Pendidikan Jasmani Olahraga Dan Kesehatan Terhadap Pelaksanaan Program Usaha Kesehatan Sekolah (UKS) Di Sekolah Dasar - Muliadi Muliadi (Universitas Negeri Makassar, 2018)
The role of Sports and Health Physical Education Teachers (Penjasorkes) has a very vital task in the school environment, as well as being an educator and mentor as well as implementing and motivating the implementation of the School Health Business (UKS) program. Moreover, most Penjasorkes teachers in elementary schools (SD) are also concurrently serving as UKS supervisors, so whether or not UKS program implementation runs depends on the attitude of the physical education teachers as UKS coaches. Facilities and infrastructures are the main tools and support for the implementation of the program from a process that will then achieve the goals that want to achieve an activity. Good state of infrastructure and facilities strongly supports its role in school progress. One of them is the role of sports and health physical education teachers in the implementation of the UKS program, because the responsibility and management of UKS and health education are more held by physical education teachers.